2007
DOI: 10.1002/jgm.1003
|View full text |Cite
|
Sign up to set email alerts
|

Targeted retroviral gene delivery using ultrasound

Abstract: We have established the basis of a novel retroviral vector technology incorporating favourable aspects of existing viral and non-viral gene delivery vectors. In particular, transduction can be controlled by means of ultrasound exposure. The technology is ideally suited to targeted delivery following systemic vector administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…The technique of tuning the ultrasound application to selectively excite microbubbles to control sonoporation should be applicable as a general delivery strategy for many impermeant agents of relevance (12)(13)(14)(15) into selected individual cells with subcellular precision. This approach has the advantage that it requires no physical isolation of cells and/or specialized micronscale fabrication and instrumentation, which are time-consuming and technically challenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique of tuning the ultrasound application to selectively excite microbubbles to control sonoporation should be applicable as a general delivery strategy for many impermeant agents of relevance (12)(13)(14)(15) into selected individual cells with subcellular precision. This approach has the advantage that it requires no physical isolation of cells and/or specialized micronscale fabrication and instrumentation, which are time-consuming and technically challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Without the need to use viral vectors, sonoporation enables the delivery of a wide range of bioactive agents with minimal inflammatory and immunological responses for both in vitro studies and in vivo applications (12)(13)(14)(15)(16). In addition, ultrasound application can be targeted to a specific volume of tissue in vivo noninvasively.…”
mentioning
confidence: 99%
“…[22][23][24][25][26][27] Shohet et al 23 demonstrated a successful transfection of rat myocardium in vivo by UTMD of MBs containing an adenovirus encoding a beta-galactosidase reporter gene. Transfection efficiencies by US with retrovirus were enhanced 6.6-fold, 4.8-fold, 2.3-fold and 3.2-fold in 293T cells, BAECs, RASMCs and L6 cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Briefly, signal from a waveform generator (model 33220A, Agilent Technologies Inc., Loveland, CO, USA) was fed into an RF power amplifier (58 dB gain, model BT00500 BETA, Tomco Technologies, Norwood, Australia) and thence to a custom-made 1 MHz ultrasound transducer (Imasonics, Besancon, France). The transducer was spherically focused, of 20 mm diameter and 68% bandwidth, with the focal point of the ultrasound beam 67 mm from the transducer face.…”
Section: Ultrasonic Exposure Of the Sie Flapmentioning
confidence: 99%
“…SonoVue is an ultrasound contrast agent consisting of phospholipid-encapsulated microbubbles (1-12 mm) filled with SF 6 gas. 30,31 SonoVue was prepared according to the manufacturer's protocol to yield a solution containing 2 Â 10 8 -5 Â 10 8 microbubbles per ml.…”
Section: Ultrasonic Exposure Of the Sie Flapmentioning
confidence: 99%